Zwitterionic Polymer‐Grafted Superhydrophilic and Superoleophobic Silk Fabrics for Anti‐Oil Applications. Issue 21 (20th May 2020) - Cheng, Yan; Wang, Jilei; Li, Minglun; Fu, Fanfan; Zhao, Yan; Yu, Jing
Abstract: A highly anti‐oil fabric membrane is synthesized by surface grafting of zwitterionic poly(sulfobetaine methacrylate) (PSBMA) onto the fabric surface. The fabric membrane is first enzymatically modified to create more reactive amine groups on the surface. A surface‐initiated atom transfer radical polymerization (SI‐ATRP) reaction is then performed to modify the fabric membrane surface with a dense PSBMA brush layer. Surface characterization indicates that the brush‐grafted fabric membrane exhibits increased surface roughness and improved superhydrophilicity. The PSBMA‐modified silk fabrics show a very large contact angle for oil droplets in water, and have excellent oil resistance in air and in water–oil mixtures. Abstract : A highly anti‐oil fabric membrane is developed by surface grafting of zwitterionic poly(sulfobetaine methacrylate) (PSBMA) onto enzymatically modified fabric surface via surface‐initiated atom transfer radical. The PSBMA‐modified fabric membrane exhibits increased surface roughness and improved superhydrophilicity. The fabrics also show excellent oil resistance in air and in water–oil mixtures.